PELECEHAN SEKSUAL ANAK JALANAN MENURUT UNDANG-UNDANG PERLINDUNGAN ANAK NO 35 TAHUN 2014 - Atmari Atmari (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
The phenomenon of street children in Indonesia must immediately receive special attention and management, considering that children are the assets of the next generation of the nation, all Indonesian children including street children must receive a portion of attention as children's rights and protection from parents, families, communities and especially the government. The number of street children in Indonesia is still so high, and all the consequences that must be faced by street children from violence to sexual harassment and free sex, they live on the streets to sustain life without protection from their parents, family and the state, they experience traumatic events that will influence the behavior and mindset of children in adulthood from the description of the facts on the ground how the form of state protection against street children who experience sexual harassment and sanctions for perpetrators of sexual crimes. This research is normative with a normative juridical approach by examining problems with the law as the main legal material as well as legal material outside the law which is then described as a result of research and the implementation of child protection covering various fields of life services must be done together, requires a coordinating organization. Implementation of child protection. Guarantees for the implementation of child protection must be carried out in various ways, among others by laws and regulations and the obligation of every member of the community, citizen to participate in child protection. Sanctions based on the provisions in Law Number 35 of 2014 and additional punishments of castration, installation of chips and so on, are likely to have a deterrent effect for perpetrators of sexual violence against minors, especially for street children